Handbook of Quantitative Criminology
XIII, 787 p. 94 illus.
Keywords: The Handbook of Quantitative Criminology is designed to be the authoritative volume on methodological and statistical issues in criminology and criminal justice. At a time when this field is gaining in sophistication and dealing with ever more complex empirical problems, this volume seeks to provide readers with a clear and up to date guide to quantitative criminology. Authored by leading scholars in criminology/criminal justice, the Handbook contains 35 chapters on topics in the following key areas: (1) research design, (2) experimental methods, (3) methods for overcoming data limitations, (4) innovative descriptive methods, (5) estimation techniques for theory and policy, (6) topics in multiple regression, and (7) new directions in statistical analysis. The contributions are written to be accessible to readers with a basic background in statistics and research methods, but they also provide a cutting edge view of statistical and methodological problems and questions. This book will be the go-to book for new and advanced methods in the field that will provide overviews of the key issues, with examples and figures as warranted, for students, faculty, and researchers alike.